A Strategic Procurement Concept for Physical Asset Management Framework - Jeeva, Ananda; Baswaid, Ahmed (IEOM, 2014)
Physical asset management has been described from a variety of different perspectives including management, engineering, operations and finance. Regardless of the increased attention paid to physical Asset Management by practitioners, academic literature still has gaps in identifying the challenges and obstacles for Asset Management. Few studies have been conducted in the area of physical Asset Management and little attention has been received on the Oil & Gas sector. This conceptual paper proposes the development of a physical Asset Management framework from two perspectives: Supply Risk (SR), and Strategic Procurement (SP). It focuses on how both perspectives can create value for Asset Management. This proposal will also examine how SR and SP can overcome the challenges and obstacles in Asset Management. It combines Reliability Theory (RT) and Business Continuity Theory (BCT) to build a theoretical foundation to formulate a physical Asset Management framework.